Do we need a sign on every rock in the water? Standard of care in negligence and the Tourism Industry in Western Australia - Sadler, Pauline (2004)
If a tourist is accidentally injured while visiting Western Australia, he or she may seek damages in the tort of negligence. The Civil Liability Act 2002 (WA) (CLA 2002), based on the Ipp Report, has altered the legal position with respect to such claims. This article examines the CLA 2002, and offers the tourism industry in Western Australia some insight into the effect of the Act. The Occupiers' Liability Act 1985 (WA) is also discussed. Cases referred to include Australian Safeway Stores v Zaluzna (1987) 162 CLR 479, Wyong Shire Council v Shirt(1980) 146 CLR 40 and Nagle v Rottnest Island Authority (1993) 177 CLR 423.